Determinants of Pneumonia Incidence Based on Inpatient Medical Records: Faktor-Faktor yang Mempengaruhi Insidensi Pneumonia Berdasarkan Catatan Medis Pasien Rawat Inap - Santoso, Noviva Maulita; Putra, Dony Setiawan Hendyca; Suyoso, Gandu Eko Julianto (Universitas Muhammadiyah Sidoarjo, 2025)
Pneumonia is a serious inflammation of lung tissue caused by attacks from pathogens. At Kaliwates General Hospital Jember, pneumonia consistently ranked among the top 10 diseases from 2022-2024 and was the most frequently diagnosed condition, with a total of 3,570 cases. This study aims to analyze the determinant factors for pneumonia incidence, namely age, severe illness causing weakness, chronic respiratory diseases, prolonged bed rest, malnutrition, and respiratory infections viral infections. A case control study design was applied using 225 inpatient medical record for the pneumonia group and 225 for the control group, selected using quota sampling technique. Data analysis used univariate and bivariate (chi-square test). The results of the chi-square test showed a significant association in the variables of severe pain causing weakness (p-value = 0.020; OR = 2.237), chronic respiratory disease (p-value = 0.000; OR = 69.023), prolonged bed rest (p-value = 0.015; OR = 10.419), malnutrition (p-value = 0.000; OR = 5.335) with pneumonia. In conclusion, the determinants of pneumonia incidence were severe illness causing weakness, chronic respiratory disease, prolonged bed rest and malnutrition.This research is expected to be used as information to cope with the increased morbidity and mortality rate of pneumonia.